Strategic Management in Improving Teachers Pedagogical Competence in Ponggok Primary School - Rahmawati, Anita Zuli (EDUKASI: Jurnal Pendidikan Islam, 2017)
ThisÃÂ  researh ÃÂ baseÃÂ  onÃÂ  quality of educationÃÂ  in Indonesia has been developing, with various programs undertaken ÃÂ byÃÂ  the ÃÂ government ÃÂ to ÃÂ continue ÃÂ improving ÃÂ the quality of education and quality of educators. This research is a qualitative research, the researcher does not use statistical data in data collection and analysis. The data needed in this study is the qualitative data, using a descriptive approach that is research that intends to make a description of the situations or events. The results of this research are that teacher pedagogic competence is the ability of teachers in managing learners learning that includes understanding of learners, planning and implementation of learning, evaluation of learning outcomes, and development of learners to actualize the various potentials it has. The application of ten pedagogic competence indicators, it is generally known that the pedagogical competence of the teachers of SDN Ponggok is sufficient, because the teachers of SDN Ponggok have prepared the lesson plan each time will teach, the RPP has been in accordance with predefined curriculum standard, using the strategy/approach appropriate, utilizing the media to enable students, master the material, process assessment and results.